Synthesis and characterization of activated carbon produced from kenaf core fiber using H3PO4 activation - M.S. Shamsuddin; N.R.N. Yusoff; M.A.Sulaiman (2016)
Kenaf core fiber (KF) which is an agricultural biomass was used to produce low-cost activated carbon using acidic chemical activating agent. The aim of this study is to find out the changes occuring in kenaf core fiber during activation with phosphoric acid (H3PO4). The surface area of the formed phosphoric acid treated kenaf core fiber activated carbon (KFAC) was determined by physical adsorption of N2 gas. Brunauer, Emmett and Teller (BET) surface area, and micropore volume values were 299.02 m2/g and 0.12 cm3/g, respectively. Fourier transform infrared (FT-IR) spectroscope analysis identified the present of carbonyls, alkenes and hydroxyls. Field Emission Scanning Electron Microscope (FESEM) image showed gradual formation of pores due to elimination of volatiles and contaminants. Powder X-ray diffraction (XRD) analysis indicated the appearance of broad diffraction background revealed predominantly amorphous structure. The proximate and ultimate analysis showed high percentage of carbon and low percentage of ash which is an indication of a good material for production of porous carbon.